Effects of online gaming intensity and school environment on students’ social behavior - Aisyah Aisyah; Suryanef Suryanef; Maria Montessori; Al Rafni (Global Econedu, 2026)
This study aimed to examine the relationships between online game playing intensity, school learning environment quality, and the social behavior of vocational high school students in Pesisir Selatan Regency. A quantitative correlational design was employed involving 221 vocational high school students selected through proportional random sampling. Data were collected using validated and reliable Likert-scale questionnaires measuring online game playing intensity, school learning environment quality, and social behavior. Data were analyzed using simple and multiple correlation and regression analyses with SPSS. The findings revealed that online game playing intensity was positively and significantly related to social behavior (r = 0.442, p < 0.05), contributing 21.5% to the variance. The school learning environment also showed a positive and significant relationship with social behavior (r = 0.487, p < 0.05), contributing 23.7%. Simultaneously, both variables significantly predicted social behavior (R = 0.489, p < 0.05), explaining 23.9% of the variance. Online game playing intensity and school learning environment quality are significant factors associated with the social behavior of vocational high school students.